A Teaching Design of “Construction-Chunk” for Chinese Comparative Sentences to Indonesian Adult Chinese Learners: 面向印尼成年汉语学习者的汉语比较句 “构式—语块” 教学设计 - Phanata, Stephanie; Phanata , Stephanie; Anqi, DING (Mandarinable: Journal of Chinese Studies, 2025)
Based on the analysis and teaching methods of “Construction-Chunk”, this paper designs a teaching plan for comparative sentences for Indonesian adult Chinese as a second language learners. The basic ideas are as follows: by comparing the “HSK Standard Course Level 2” and the survey interviews on Indonesian adult Chinese comparative sentences, the grammatical items of comparative sentences that need to be studied are determined; the errors are analyzed in connection with the characteristics of the two aspects of teaching, and the problems that need to be solved in this teaching design are determined; then, according to the analysis and teaching methods of “Construction-Chunk”, and referring to the adult second language acquisition theory, the teaching design of Chinese comparative sentences for Indonesian students is carried out. Through qualitative research, the characteristics of the “Construction-Chunk” teaching method are reflected in the Chinese teaching design, which is conducive to reducing word order errors when learning such comparative sentences for Indonesian adult Chinese second language learners, and developing a new method of learning Chinese.